Konzeptionierung eines digitalen Wissensmanagementsystems für die zivile Gefahrenabwehr am Beispiel der Feuerwehr - Schultz, Andreas Maximilian
Wissensmanagement ist im unternehmerischen Kontext ein etabliertes Feld der Forschung und Praxis, das auf die Verbesserung von Effizienz und Wettbewerbsfähigkeit abzielt. In den Organisationen der zivilen Gefahrenabwehr hingegen gibt es erhebliche Defizite bei der Erfassung und Weitergabe von Wissen, obwohl auch hier große Abhängigkeiten vom Erfahrungswissen bestehen. Diese Arbeit analysiert am Beispiel der Feuerwehr die Gründe für diese Diskrepanz und entwickelt ein Konzept, das das Wissensmanagement im Feuerwehrwesen nachhaltig verankern soll. Eine deutschlandweite Umfrage mit 577 Einsatzkräften ergab, dass eine digitale Verwaltungsunterstützung bereits verbreitet ist, das Wissen jedoch vornehmlich per E-Mail, Chat, mündlich oder per Aushang verteilt wird. Die Teilnehmenden wünschen sich eine Lösung für das Wissensmanagement, die im Einsatz, bei Aus- und Weiterbildung sowie der Verwaltungsarbeit unterstützt. Auf der Umfrage und einer systematischen Literaturrecherche aufbauend, wurde der Handlungsbedarf identifiziert. Darauf basieren die Ableitung der Anwendungsbereiche sowie Rahmenbedingungen, welche sich in den Anforderungen an ein Wissensmanagementsystem widerspiegeln. Das Umsetzungskonzept beschreibt die Systemarchitektur der Lösung, die auf einem open-source Wiki mit passenden Erweiterungen beruht. Zentrales Element ist die Möglichkeit zum Austausch von Wissen über Organisationsgrenzen. Abgeschlossen wird die Arbeit mit der Demonstration und Evaluation der Lösung.

Thermo-Hydraulic Performance of Pillow-Plate Heat Exchangers with Streamlined Secondary Structures: A Numerical Analysis - Afsahnoudeh, Reza; Riese, Julia; Kenig, Eugeny Y. (Systems and Control Transactions)
Pillow-plate heat exchangers (PPHEs) represent a viable alternative to conventional shell-and-tube and plate heat exchangers. The waviness of their channels intensifies fluid mixing in the boundary layers and facilitates heat transfer. Applying secondary surface structuring can further enhance the overall thermo-hydraulic performance of PPHEs, thus increasing their competitiveness against conventional heat exchangers. In this work, streamlined secondary structures applied on the PPHE surface were studied numerically to explore their potential in enhancing near-wall fluid mixing. Computational fluid dynamics (CFD) simulations of single-phase turbulent flow in the inner PPHE channel were performed and pressure drop, heat transfer coefficients, and overall thermo-hydraulic efficiency were determined. The simulation results clearly demonstrate a favourable influence of secondary structuring on the heat transfer performance of PPHEs.

A Data-Driven Conceptual Approach to Heat Pump Sizing in Chemical Processes with Fluctuating Heat Supply and Demand - Hochhaus, Thorben; Wloch, Johannes; Grünewald, Marcus; Riese, Julia (Systems and Control Transactions)
Heat pumps play a crucial role in decarbonizing the chemical industry. The integration and sizing of heat pumps in chemical processes is a challenging task in multi-product chemical processes due to the fluctuating waste heat supply and heat demand. Integrating heat pumps may require a retrofit of the utility system. Mathematical optimization is a useful tool to tackle this challenge by enabling the analysis of correlation between relevant system parameters and equipment sizing. This study demonstrates the utilization of mathematical optimization and parameter studies for utility system equipment sizing addressing fluctuating heat supply and demand profiles.

Towards Practicable Algorithms for Rewriting Graph Queries Beyond DL-Lite - Löhnert, Bianca; Augsten, Nikolaus; Okulmus, Cem; Ortiz, Magdalena (The Semantic Web - 22nd European Semantic Web Conference, ESWC 2025, Portoroz, Slovenia, June 1-5, 2025, Proceedings, Part I)
Despite the advantages that the virtual knowledge graph paradigm has brought to many application domains, state-of-the-art systems still do not support popular graph database management systems like Neo4j. Their query rewriting algorithms focus on languages like conjunctive queries and their unions, which were developed for relational data and are poorly suited for graph data. Moreover, they also limit the expressiveness of the ontology languages that admit rewritings, restricting them to those that enjoy the so-called FO-rewritability property. Rewritings have thus focused on the DL-Lite family of Description Logics. In this paper, we propose a technique for rewriting a family of navigational queries for a suitably tailored fragment of ELHI. Leveraging navigational features in the target query language, we can include some widely-used axiom shapes not supported by DL-Lite. We implemented a proof-of-concept prototype that rewrites into Cypher queries, and tested it on a real-world cognitive neuroscience use case with promising results.
Keywords: Ontology-based Data Access; Property Graphs; Navigational Queries

Evaluation of piezoelectric micromachined ultrasonic transducers (PMUT) for the broadband detection of ultrasonic elastic waves - Zeipert, Henning; Claes, Leander; Stoeckel, Chris; Mulay, Shubham; Henning, Bernd

Digitale Kompetenzen für Lehrkräfte in der beruflichen Bildung – Beiträge zur Modellierung, Messung und Förderung - Sänger, Niklas
Die digitale Transformation stellt Lehrkräfte vor eine doppelte Herausforderung: Sie sind selbst Lernende im Zuge des Wandels und gleichzeitig dafür verantwortlich, digitale Kompetenzen bei ihren Lernenden zu fördern. Aus Sicht der beruflichen Bildung besteht eine weitere Herausforderung darin, dass Lehrkräfte zwischen zwei inhaltlichen Referenzsystemen – wissenschaftsorientiertem Fachwissen und praxisbezogenem beruflichem Wissen – vermitteln müssen. Bisherige Forschungsarbeiten fokussieren jedoch primär medienpädagogische Aspekte und vernachlässigen den Einfluss der digitalen Transformation auf die fachlichen Lerngegenstände sowie damit verbundene fachdidaktische Implikationen. Die Dissertation adressiert diese Forschungslücke, indem sie untersucht, wie digitale Kompetenzen von Lehrkräften in der beruflichen Bildung konzeptualisiert, empirisch erfasst und curricular integriert werden können. Sie verfolgt dabei drei zentrale Fragestellungen: (1) Wie lassen sich digitale Kompetenzen im Kontext des doppelten Gegenstandsbezugs theoretisch fundieren? (2) Wie kann ein entsprechendes Kompetenzmodell empirisch operationalisiert werden? (3) Welche Implikationen ergeben sich daraus für die curriculare Gestaltung von Lehramtsstudiengängen? Im Rahmen der kumulativen Dissertation wird zunächst das TPACK-Modell kritisch analysiert und für den Kontext der beruflichen Bildung erweitert. Darauf aufbauend wird ein Messinstrument zur Erfassung digitaler Kompetenzen entwickelt und empirisch validiert. Zudem wird ein hochschuldidaktisches Konzept zur curricularen Integration digitaler Kompetenzen entwickelt und reflektiert. Die Ergebnisse zeigen, dass der doppelte Gegenstandsbezug ein zentrales Strukturmerkmal digitaler Kompetenzen in der beruflichen Bildung darstellt und bei der Ausbildung von Lehrkräften systematisch berücksichtigt werden muss. Die Dissertation leistet einen konzeptionellen und empirischen Beitrag für den Diskurs um digitale Kompetenzen in der beruflichen Bildung und gibt konkrete Impulse für die Professionalisierung von Lehrkräften im Zuge der digitalen Transformation.

Ultrasonic phased array interface using programmable I/O and microprocessor clock synchronisation - Nellius, Tom; Henne, Kevin; Hartinger, Maximilian; Meihost, Lars; Hetkämper, Tim; Zeipert, Henning; Claes, Leander; Henning, Bernd

Innovation und Transfer in der kommunalen Bildungsarbeit. Erfahrungen aus zehn Jahren wissenschaftlicher Begleitung der Transferinitiative Kommunales Bildungsmanagement - Euler, Dieter; Sloane, Peter F. E.; Jenert, Tobias; Daniel-Söltenfuß, Desiree; Hagemeier, Daniel; Ludolph, Fabian; Fuhrmann, Joelle

Evolving Design for Assembly, Disassembly and Reassembly into a new paradigm: Design-for-Capabilities with Hybrid Decision Support as an enabler for circular products - Gräßler, Iris; Pottebaum, Jens; Nyhuis, Peter; Schmidt, Matthias; Grewe, Benedikt; Vollenkemper, Felix; Hesse, Thomas; Meinecke, Tim (Stuttgarter Symposium für Produktentwicklung (SSP) 2025)

Scholarship of Teaching and Learning und disziplinäre Forschung: Eine komplexe Beziehung

Transformation durch Vermittlung. Das Heilige in der Geschichte pädagogischen und literarischen Wirkens der Jesuiten in Lateinamerika - Freitag, Christine; Thiem, Annegret ((Un)verfügbar - Kulturen des Heiligen)

Materialschonende Verarbeitung von Thermoplasten auf Wave-Schnecken - Schall, Christoph Wilhelm Theodor
Die Extrusion stellt das mengenmäßig dominante Verarbeitungsverfahren für thermoplastische Kunststoffe dar. Daher gibt es starke Bestrebungen in diesem Bereich hin zu einer höheren Wirtschaftlichkeit, welche beispielsweise durch höheren Massedurchsatz bei gleichbleibender Maschinengröße erreicht werden kann, oder aber auch im Hinblick auf eine Kreislaufwirtschaft die Bestrebung hin zu einer materialschonenden Verarbeitung. Beide Bestrebungen erfordern spezielle Schneckenkonzepte. Hierunter fallenWave- Schnecken, welche in beiden Bereichen ein vorteilhaftes Prozessverhalten aufzeigen sollen. Die Auslegung von Wave-Schnecken erfordert jedoch ein stärkeres Verständnis über das geometrieabhängige Prozessverhalten in der Extrusion. Im Rahmen der Dissertation werden zwei Themengebiete angegangen. Das erste Thema ist die Herleitung einer Methode zur Charakterisierung des Abbauverhaltens von Thermoplasten sowie die Nutzung der Charakterisierung als Vorhersagemodell. Das zweite Thema behandelt die Auslegung von Wave-Schnecken basierend auf numerischen Simulationen samt Validierung anhand von sieben Energy-Transfer-Schnecken im Vergleich zu drei konventionellen Schnecken. Hierbei werden unter anderem der Materialabbau, die thermische und die stoffliche Homogenität betrachtet, um ein umfassendes Bild über das Prozessverhalten der Schnecken zu schaffen. Die vorgestellten Untersuchungen dienen schlussendlich zu einer Bestätigung des vorteilhaften Prozessverhaltens von Wave-Schnecken.

Du Châtelet, Induction, and Newton’s Rules for Reasoning - Wells, Aaron (European Journal of Philosophy)
I examine Du Châtelet’s methodology for physics and metaphysics through the lens of her engagement with Newton’s Rules for Reasoning in Natural Philosophy. I first show that her early manuscript writings discuss and endorse these Rules. Then, I argue that her famous published account of hypotheses continues to invoke close analogues of Rules 3 and 4, despite various developments in her position. Once relevant experimental evidence and some basic constraints are met, it is legitimate to inductively generalize from observations; general hypotheses can thereafter be assumed as true until contrary experiments show otherwise. I conclude by arguing that this account of induction plays an essential role in her metaphysics, both in an argument for simple substances—which has an inductive premise—and in her attempt to distinguish acceptable and unacceptable metaphysical commitments.

Fast model-based calibration of multiple injections for a CI engine using nonlinear optimal control - Moretto, Giordano; Schnell, Nicolas; Frey, Jonathan; Karakaya, Yasin; Amstutz, Alois; Diehl, Moritz; Kasper, Tina; Onder, Christopher (Control Engineering Practice)

Gottes Treue zu Israel (Röm 9–11) - Taschl-Erber, Andrea; Woppowa, Jan (Elementare Bibeltexte)

Corrosion behaviour of self-piercing riveted joints with uncoated rivets in high nitrogen steel - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Production Engineering)

Maghemite nanoparticles synthesis via spray flame synthesis and particle characterization by hole in a tube sampling and scanning mobility particle sizing (HIAT-SMPS) (Applications in Energy and Combustion Science)
In order to standardize spray flame synthesis (SFS) studies, intensive work has been done in recent years on the design of burner types. Thus, in 2019, the so-called SpraySyn1 burner was introduced (SS1), which was subsequently characterized in numerical and experimental studies. Based on this research, a modification of the nozzle design was proposed, which has now been considered in the successor model, SpraySyn2 (SS2). As little is known about the effect of the nozzle adaptation on the particle formation, we operated both burners under identical operating conditions to produce maghemite. The final powder comparison showed that SS2 yielded considerable higher specific surface areas (associated with smaller primary particle sizes), lower polydispersity, and higher phase purity. To obtain further information on the size distributions of aggregates and agglomerates generated by SS2, aerosol samples were extracted by hole in a tube (HIAT) sampling and characterized by scanning mobility particle sizing (SMPS). Samples were extracted along the centerline at different heights above the burner (HAB) above the visible flame tip (>7 cm), and quenching experiments were performed to extract the aerosol samples at different dilution rates. Thereby, it was demonstrated that performing detailed quenching experiments is crucial for obtaining representative HIAT-SMPS data. In particular, agglomerates/aggregate sizes were overestimated by up to ~70 % if samples were not sufficiently diluted. If sufficient dilution was applied, distribution widths and mean particle mobility diameters were determined with high accuracy (sample standard derivation <5 %). Our data suggested the evolution of primary particle sizes was mostly completed <7 cm HAB and it was shown aggregates/agglomerates present above the visible flame were compact in structure (non- fractal). The mean diameter of the particle ensemble grew along the centerline from 6.9 nm (7 cm) to 11.4 nm (15 cm), while distribution widths grew from 1.42 to 1.52.
Keywords: Flame Spray Pyrolysis; SpraySyn2; Spray flame synthesis; Maghemite nanoparticles; Gas to particle-conversion; Hole in a tube sampling

„Es nimmt der Raum gastfreundlich auf die Menge“. Theodor Hells Prolog zur Eröffnung des Dresdner Hoftheaters (1841) - Eke, Norbert Otto (Die Kunst der Theatereröffnung. Ästhetik und Sozialgeschichte von Bühnenprologen)

Qualitätsoffensive Ganztag - Praktische Methoden für den Weg zur guten Ganztagsbildung - Seitz, Simone; Hamacher, Catalina; Schieffer, Leonie; Bunte, Charline

Stickstoff basierte Flammschutzmittel für das Lasersintern: Optimierung und Analyse der Recyclingfähigkeit (Studienarbeit) - Hücker, Lars